The Aggressive Behaviour in Sports Among Athletes In A Public University (Sains Humanika, 2021)
Collegiate athletes displayed different aggressive tendencies in an off-field situation based on the sports that they play. This study was conducted to identify the level and differences of aggressive behavior among athletes in a public university in Malaysia. A total of 91 student-athletes that represented different types of sports participated in this study. The instrument used to measure the aggressive behaviour among athletes was the Aggression Questionnaire. Descriptive statistics were used to identify the level of aggressive behaviour and the independent t-test was used to analyze the differences of aggressive behaviour based on demographic factors such as gender and types of sports. The findings revealed that the level of aggressive behaviour among athletes in the university are at a low level and there is no significant differences in aggressive behaviour based on gender and types of sports. This study contributes to the literature on the aggressive behavior in the context of student-athletes in higher education institution.
Keywords: Aggressive behaviour, student athlete, off-field aggression, sport